Long-term Effects of a Brief Mindfulness Intervention Versus a Health Enhancement Program for Treating Depression and Anxiety in Patients Undergoing Hemodialysis: A Randomized Controlled Trial. (February 2022) - Rigas, Christina; Park, Haley; Nassim, Marouane; Su, Chien-Lin; Greenway, Kyle; Lipman, Mark; McVeigh, Clare; Novak, Marta; Trinh, Emilie; Alam, Ahsan; Suri, Rita S.; Mucsi, Istvan; et al.
Background: Depression and anxiety affect approximately 50% of patients with kidney failure receiving hemodialysis and are associated with decreased quality of life and increased risk of hospitalization and mortality. A Brief Mindfulness Intervention (BMI) may be promising in treating depressive and anxiety symptoms in this population, but the long-term sustainability of the intervention's effects is unknown. Objective: We previously conducted a randomized controlled trial (RCT; n = 55) comparing an 8-week BMI with an active control (Health Enhancement Program [HEP]) for patients receiving dialysis, with depression and/or anxiety. Here, we examine the 6-month follow-up data to determine the long-term sustainability of BMI versus HEP in reducing (1) depressive symptoms, (2) anxiety symptoms, and (3) the efficacy of BMI versus HEP in reducing the likelihood of hospitalization. Design: In this study, we analyzed 6-month follow-up data from an 8-week assessor-blinded parallel RCT, which evaluated the efficacy of a BMI against an active control, HEP, in patients receiving hemodialysis with symptoms of depression and/or anxiety. Setting: The study took place at hemodialysis centers in 4 tertiary-care hospitals in Montreal, Canada. Participants: Participants included adults aged ≥18 years who were receiving in-center hemodialysis 3 times per week and had symptoms of depression and/or anxiety as indicated by a score ≥6 on the Patient Health Questionnaire–9 (PHQ-9) and/or the General Anxiety Disorder–7 (GAD-7). Methods: Participants were randomized to the treatment arm (BMI) or the active control arm (HEP) and completed assessments at baseline, 8 weeks, and 6-month follow-up. Depression was assessed using the PHQ-9, and anxiety was assessed by the GAD-7. Hospitalization rates were assessed using medical chart information. Results: We observed significant decrease in depression scores over 6 months in both BMI and HEP groups, with no significant difference between groups. Anxiety scores significantly decreased over 6 months, but only in the BMI group. Brief Mindfulness Intervention and Health Enhancement Program were comparable in terms of hospitalization rates. Limitations: The limitations of our study include the modest sample size and lack of a third arm such as a waitlist control. Conclusions: Our results suggest that the beneficial effects of BMI and HEP for improving mood disorder symptoms in patients receiving dialysis persist at 6-month follow-up. Both interventions showed sustained effects for depressive symptoms, but BMI may be more useful in this population given its efficacy in reducing anxiety symptoms as well. Trial registration: Prior to recruitment, the trial had been registered (ClinicalTrials.gov Identifier: NCT03406845).